What is it to practise good medical ethics? A Muslim's perspective - Serour, G. I. (Journal of medical ethics, 2015)
Good medical ethics should aim at ensuring that all human beings enjoy the highest attainable standard of health. With the development of medical technology and health services, it became necessary to expand the four basic principles of medical ethics and link them to human rights. Despite the claim of the universality of those ethical principles, their perception and application in healthcare services are inevitably influenced by the religious background of the societies in which those services are provided. This paper highlights the methodology and principles employed by Muslim jurists in deriving rulings in the field of medical ethics, and it explains how ethical principles are interpreted through the lens of Islamic theory. The author explains how, as a Muslim obstetrician-gynaecologist with a special interest in medical ethics, including international consideration of reproductive ethics issues, he attempts to ‘practise good medical ethics’ by applying internationally accepted ethical principles in various healthcare contexts, in ways that are consistent with Islamic principles, and he identifies the evidence supporting his approach. He argues that healthcare providers have a right to respect for their conscientious convictions regarding both undertaking and not undertaking the delivery of lawful procedures. However, he also argues that withholding evidence-based medical services based on the conscientious objection of the healthcare provider is unethical as patients have the right to be referred to services providing such treatment.